Peran Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Sekolah Menengah Pertama (SMP) Di Kabupaten Muko-Muko Provinsi Bengkulu - Warto Warto; Khairiah Khairiah (Al-Khair Journal : Management, Education, and Law, 2022)
Abstract:The quality of junior high school education in the Muko-muko Regency is still relatively weak because the principal has not played an optimal role. The purpose of this paper is to map and analyze the quality of education, the relationship of the role of the principal with the quality of education, and the role of the principal can improve the quality of education. Using descriptive qualitative methods. The results show that the role of the principal can improve the quality of school education. Then it can be concluded; (1) The quality of school education, in general, has been good, but the principal has not been able to give full confidence to the teacher in carrying out the task, thus affecting the quality; (2) The relationship of the principal with the quality of education, namely the quality of school education is determined by the principal and professional teachers so that the development of improving the quality of educators and education personnel becomes better, and the quality of education in schools becomes improved; and (3) The role of the principal has a big impact on the education management process and the quality of management affects the quality of education. A highly competitive school becomes everyone's dream. To achieve the quality of high-competitive schools, one of the determining factors is the optimization of the role of the principal. Thus it can be suggested, that if you want to improve the quality of education then increase the role of the principal.Keywords: Quality of Education, Role of Principal, Quality of Junior High School.Abstrak: Mutu pendidikan sekolah menengah pertama di Kabupaten Muko-muko masih tergolong lemah dikarenakan kepala sekolah belum berperan secara optimal. Tujuan tulisan ini untuk memetakan dan menganalisis bentuk mutu pendidikan, hubungan peran kepala sekolah dengan mutu pendidikan, dan peran kepala sekolah dapat meningkatkan mutu pendidikan. Menggunakan metode kualitatif deskriptif. Hasil menunjukkan bahwa peran kepala sekolah dapat meningkatkan mutu pendidikan sekolah. Maka dapat disimpulkan bahwa; (1) Bentuk mutu pendidikan sekolah secara umum telah baik, namun pada kepala sekolah belum mampu memberikan kepercayaan penuh kepada guru dalam melaksanakan tugas, sehingga mempengaruhi mutu; (2) Hubungan kepala sekolah dengan mutu pendidikan yaitu mutu pendidikan sekolah ditentukan oleh kepala sekolah dan guru yang profesional, sehingga pembinaan peningkatkan mutu tenaga pendidik dan tenaga kependidikan menjadi lebih baik, dan mutu pendidikan di sekolah menjadi meningkat; dan (3) Peran kepala sekolah berdampak besar bagi proses pengelolaan pendidikan dan mutu pengelolaan mempengaruhi mutu pendidikan. Sekolah yang berdaya saing tinggi menjadi idaman semua orang. Untuk mencapai mutu sekolah yang berdaya saing tinggi, salah satu faktor penentu adalah optimalisasi peran kepala sekolah. Dengan demikian dapat disarankan, jika ingin meningkatkan mutu pendidikan maka tingkatkanlah peran kepala sekolah.Kata Kunci: Mutu Pendidikan, Peran Kepala Sekolah, Mutu Sekolah Menengah Pertama.